Thrombocytopenia and Plasmodium falciparum malaria in children with different exposures. Issue 6 (1st June 2003) - Moulin, F; Lesage, F; Legros, A-H; Maroga, C; Moussavou, A; Guyon, P; Marc, E; Gendrel, D
Abstract : We studied thrombocytopenia during acute Plasmodium falciparum malaria in 64 traveller children from Paris (France), 85 children from Dakar (Senegal) with an intermittent exposure (69 with severe attack or cerebral malaria), and 81 children from Libreville (Gabon) with a perennial exposure (43 with severe attack or cerebral malaria). Initial thrombocytopenia was present in 43–58% of children with P falciparum malaria but was not more frequent in severe outcome or cerebral malaria. Low parasitaemia may lead to the misdiagnosis of malaria and delayed treatment when there is associated thrombocytopenia